2013
DOI: 10.1016/j.ibusrev.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The formation of trust and commitment in business relationships in the Middle East: Understanding Et-Moone relationships

Abstract: Abstract:In recent years, different forms of relationships that are culturally bond have emerged such as; "Guanxi' in China (Yau, Lee, Chow, Sing, and Tse, 2000; Lou, 2007;Liu, Li, Tao and Wang, 2008), "Blat' in Russia (Michailova and Worm, 2003) and "Boon Koon' in Thailand (Pimpa, 2008). While these special forms of relationships are culturally bond, studies have also suggested that the development of a business relationship is directly linked to the development of trust and commitment (Wilson, 1995). Conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
127
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(134 citation statements)
references
References 104 publications
(124 reference statements)
3
127
1
3
Order By: Relevance
“…Researchers demonstrate growing interest in trust-commitment theories within the realm of international business (Abosag and Lee 2013, Bloemer et al 2013, Friman et al 2002. However, studies on this subject remain too limited to warrant conclusive results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers demonstrate growing interest in trust-commitment theories within the realm of international business (Abosag and Lee 2013, Bloemer et al 2013, Friman et al 2002. However, studies on this subject remain too limited to warrant conclusive results.…”
Section: Discussionmentioning
confidence: 99%
“…Authors agree with Sankowska (2013: 87) on the premise that trust "…leads people to engage in risk taking behaviors…" Authors believe that a trust based-relationship reduces the need for a formal contract and the costs of the relationship's governance. In such a relationship, partners are less likely to demonstrate opportunistic behavior in lieu of improved cross-border performance in the future (Abosag and Lee 2013). Given this result, the firm's resources can be invested in productive matters, instead of using them to monitor opportunism.…”
Section: Mediating Effects Of Competitive Advantagementioning
confidence: 99%
See 1 more Smart Citation
“…This focus makes sense given the global economic significance of China, and of wider Chinese culture among the extensive Chinese diaspora. There have more recently been efforts to include other non-Western cultural concepts into the business, management and marketing literature; notably, Arab concepts such as wasta and et-Moone have received growing attention (Hutchings and Weir 2006;Abosag and Naudé 2014;Abosag and Lee 2013). However, from a research-design perspective, the emphasis remains largely on identifying how Western theories need to be adapted to incorporate insights into non-Western cultural concepts.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Bloemer et al (2013) pointed that in order to avoid too much cost when leaving customers, company calculatively committed to maintain their relationship with them. Therefore, Abosag & Lee (2013) revealed that calculative commitment establishes a competence trust. The study also underlined that the combination of accumulated trust, calculative commitment, and affective commitment lead customers to have the will to maintain the relationship.…”
Section: H7: Trust Has a Positive Influence On Affective Commitment Imentioning
confidence: 99%